On the Road with Texas Highways : A Tribute to True Texas - Smith, J. Griffis (Book collections on Project MUSE., 2014)
N a short line of Texas Highways distinguished photo editors, J. Griffis Smith has been described by a fellow photographer as a "galactic force," reveling in taking pictures of everything Texas wherever the magazine's assignments took him, all with the goal of inspiring "folks to travel."Celebrating the roaming life of a professional magazine photographer, Texas Highways has joined with Smith to assemble a collection of signature images from three decades of work, including memorable pictures of Texas icons, landscapes, people, and historical and cultural destinati.